PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA BUDHA SISWA KELAS V SDN 004 TEMBILAHAN KOTA KECAMATAN TEMBILAHAN - Tatik Puji Lestari (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study was conducted because of the low learning outcomes of Buddhism religious education students ofclass V SDN 004 Tembilahan Kota Kecamatan Tembilahan that has not reached the minimum completenesscriteria set that is 70. The purpose of this study is to improve the learning outcomes of Buddhist education ofstudents of grade V SDN 004 Tembilahan Kota Tembilahan by applying cooperative learning model type thinkpair share (TPS). This research was conducted in class V SDN 004 Tembilahan Kota Kecamatan Tembilahan,This research is a classroom action research (PTK) which is carried out in two cycles. The subjects of this studyare the students of grade V SDN 004 Tembilahan Kota Kecamatan Tembilahan with the number of students 16people, 10 male students and 6 female students. Based on the result of study result of student learning increasefrom base score that is with percentage mastery 37,5%, with average 63,75, increase in cycle I with percentagemastery 62,5% with average 70,31 and percentage increase 9, 33%. Increased again in cycle II is with thepercentage mastery 87.5% with an average of 78.12 and percentage increase of 18.39%.